Genetic components of human pain sensitivity: a protocol for a genome-wide association study of experimental pain in healthy volunteers. Issue 4 (20th April 2019) - Schmid, Annina B; Adhikari, Kaustubh; Ramirez-Aristeguieta, Luis Miguel; Chacón-Duque, Juan-Camilo; Poletti, Giovanni; Gallo, Carla; Rothhammer, Francisco; Bedoya, Gabriel; Ruiz-Linares, Andres; Bennett, David L
Abstract : Introduction: Pain constitutes a major component of the global burden of diseases. Recent studies suggest a strong genetic contribution to pain susceptibility and severity. Whereas most of the available evidence relies on candidate gene association or linkage studies, research on the genetic basis of pain sensitivity using genome-wide association studies (GWAS) is still in its infancy. This protocol describes a proposed GWAS on genetic contributions to baseline pain sensitivity and nociceptive sensitisation in a sample of unrelated healthy individuals of mixed Latin American ancestry. Methods and analysis: A GWAS on genetic contributions to pain sensitivity in the naïve state and following nociceptive sensitisation will be conducted in unrelated healthy individuals of mixed ancestry. Mechanical and thermal pain sensitivity will be evaluated with a battery of quantitative sensory tests evaluating pain thresholds. In addition, variation in mechanical and thermal sensitisation following topical application of mustard oil to the skin will be evaluated. Ethics and dissemination: This study received ethical approval from the University College London research ethics committee (3352/001) and from the bioethics committee of the Odontology Faculty at the University of Antioquia (CONCEPTO 01–2013). Findings will be disseminated to commissioners, clinicians and service users via papers and presentations at international conferences.